Amphiphilic polypyridyl ruthenium complexes: synthesis, characterization and aggregation studies - Bhand, Sujit; Lande, Dipali N.; Pereira, Eulalia; Gejji, Shridhar P.; Weyhermueller, Thomas; Chakravarty, Debamitra; Puranik, Vedavati G.; Salunke-Gawali, Sunita (Polyhedron, 2019)
{Synthesis and characterization of five amphiphilic ruthenium(11) complexes of the type [Ru(Cn)(3)]center dot(PF6)(2) (Cn = 4,4'-dialkyl-2,2'-bipyridine
Keywords: 2; 2 `-bipyridine; Aggregation; Amphiphilic ligand; Metallosurfactant; Ruthenium complexes